Pengaruh kualitas layanan terhadap loyalitas pelanggan restoran Jepang yang beroperasi di Kota Bandung - Danial, Jihan Nabilah; Hendayani, Ratih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The increasing number of culinary businesses in the city of Bandung makes Japanese restaurants need to pay attention to their competitive advantages so as not to lose consumers. The study was conducted to determine the direct effect of service quality on Japanese restaurants on customer satisfaction and customer loyalty and to determine the role of customer satisfaction as a mediator between service quality and customer loyalty. This study uses quantitative methods. The sampling technique used the purposive sampling method. The findings in this study indicate that service quality (quality of food, employees, prices, and the environment) has a significant positive effect on customer satisfaction. Employees, price, and environment have a significant positive effect on loyalty, but food quality has no effect on customer loyalty. Customer satisfaction has a significant positive effect on customer loyalty. Another finding is that customer satisfaction can influence service quality from employees, prices, and the environment. However, customer satisfaction cannot mediate food quality and customer loyalty in Japanese restaurants in Bandung. This study recommends that Japanese restaurants continue to improve and maintain service quality consistently so that they can continue to increase customer satisfaction, which can trigger the emergence of loyalty.